Biospeckle PIV (Particle Image Velocimetry) para analisar escoamento de fluidos - Soares, Rodrigo Reis (2011)
This work presents an alternative protocol for the adoption of the Particle Image Velocimetry (PIV) as a technique for monitoring the flow without the external addition of seed particles used as targets in cross-correlation of images of a flow. The dynamic laser speckle patterns with its grains varying in time formed the basis for the PIV application. In this case, with a pre-processing step related to the frequency approach. In order to avoid the boiling effect of the biospeckle phenomenon, which is also used to describe the dynamic laser speckle, the images collected in time were manipulated in the frequency domain by isolating the expression inside the translational signal. The hypothesis of using grains in speckle patterns to implement PIV, as well as the isolation of translational information was tested with a simulated speckle pattern on a pure translation, an actual flow of water in a translucent tube illuminated by a laser beam, and a microflow in a torn leaf in response to internal conditions of a broken pressure. The results confirmed the hypothesis that considers the use of BioSpeckle Laser (BSL) associated with the PIV technique and showed a protocol for dealingl with the boiling effect that undermines translation information in speckle patterns.